Manajemen Quality Assurance sebagai upaya Peningkatan Kepercayaan Masyarakat terhadap Sekolah Studi di MTS Hubbul Wathon Sangatta Selatan - Uswatun Umi Zarhasih; Mahfud Ifendi; Tri Velyna (Jurnal Manajemen dan Pendidikan Agama Islam, 2025)
The research method employed is a descriptive qualitative approach, with data collection techniques including observation, in-depth interviews, and documentation. Informants for this study consisted of the school principal, teachers, students, and community members. The research findings indicate the implementation of quality assurance management. First, a plan is developed related to the vision and mission as the goals to be achieved. Second, organization by the Madrasah Quality Assurance Team focuses on quality. Third, implementation involves a series of activities, such as teacher training and the implementation of a structured evaluation system. Fourth, for control, the principal and the QAT (Quality Assurance Team) actively motivate all school elements. Fifth, the guidance phase involves continuous control through periodic monitoring and evaluation of the quality assurance program's implementation, supported by the PDCA (Plan-Do-Check-Act) theory. Efforts to enhance trust include an emotional approach, offering programs that align with community needs, and consistently providing updates on student progress through social media